Determination of Chromium, Iron, Molybdenum and Silicon in Ti-Al Alloy by Inductively Coupled Plasma-Optical Emission Spectrometry with Sodium Peroxide Alkali Fusion - HUANG Chao-guan; MENG Yi-shu; GUO Huan-hua; LIN Ling-yu; YANG Chun-tao (Yankuang ceshi, 2018)
Single acid cannot completely dissolve Ti-Al alloy with high Ti content when determining chromium, iron, molybdenum and silicon by Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES). A small amount of impurity remains after dissolving the samples by mixed acid. Furthermore, the precipitation occurs readily during re-dissolution, even if using concentrated aqua regia. In this study, the Ti-Al alloys were fused with sodium peroxide for 20 min at 700℃ and were acidified by hydrochloric acid. The method for the determination of chromium, iron, molybdenum and silicon in Ti-Al alloy by ICP-OES was established. The interference from the titanium matrix in samples was improved by the titanium matrix matching method when the concentration of titanium was greater than 200 μg/mL. Additionally, the amount of salt content in solution was controlled by sodium peroxide to ensure the stability of determination. The detection limits and lower determination limits are 0.02-0.05 μg/mL and 0.07-0.17 μg/mL, respectively. The method has been verified by analyzing the national standard material (GBW02501). The relative standard deviations (RSDs) are 0.90%-4.89%, the relative errors are 1.2%-3.6% and the recoveries are 91.6%-103.8%. Compared with acid solution, the dissolution of the samples is complete using the proposed method. Moreover, the method is accurate, reliable, and suitable for multi-element determination of Ti-Al alloy with high titanium content.